Intelligent elderly health care I - Chia, Yun Zhen (2017)
In the current society, it is increasingly common for elderlies to live alone. Hence, the safety of these elderlies is important. This projects intends to improve the wellbeing of the elderlies by creating an intelligent indoor elderly care device that consists of two main functions: a fall detector and a medicine reminder. When the device detects a fall, it triggers an alarm and sends an SMS to a caregiver, requesting for immediate assistance. If the detected fall is a false alarm, the user can reset the device within a time frame, so that the SMS will not be sent out. The function of the medicine reminder is to remind the user to consume their medication. A pre-recorded voice will be played it is time for the user to take his/her medication (e.g. every 6 hours). A LCD display will also be shown as an additional reminder. It will show the medication name to be taken and its location. The use of Arduinos, Xbees, GSM, accelerometer and some other electronic devices coupled together will help in accomplishment of that.